2021
DOI: 10.1186/s12951-021-01193-9
|View full text |Cite
|
Sign up to set email alerts
|

A cascade targeting strategy based on modified bacterial vesicles for enhancing cancer immunotherapy

Abstract: Background As an efficient tumor immunotherapy, PD-1 antibody has been gradually used in clinical tumor treatment, but the low response rate and excessive immune response limit its extensive application. Results Herein, a therapeutic regime for the reinvigoration and activation of the tumor immune microenvironment is introduced to improve the anti-tumor effect of the PD-1 antibody. To comprehensively improve the effect of the immunotherapy and redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…[215] First, OMVs contain many natural adjuvant components inherited from the parent bacterium but in a nonreplicative form, which can stimulate immune maturation and initiate inflammation in a controllable manner. [180] As shown in Figure 13B, the engineered OMV-PD1 specifically expressing PD1 was isolated and purified from E. coli that specifically expressing PD1. OMV-PD1 could bind to PD-L1 on the surface of tumor cells, promote the internalization and reduction of PD-L1, and protect T cells from immunosuppression.…”
Section: Omvsmentioning
confidence: 99%
“…[215] First, OMVs contain many natural adjuvant components inherited from the parent bacterium but in a nonreplicative form, which can stimulate immune maturation and initiate inflammation in a controllable manner. [180] As shown in Figure 13B, the engineered OMV-PD1 specifically expressing PD1 was isolated and purified from E. coli that specifically expressing PD1. OMV-PD1 could bind to PD-L1 on the surface of tumor cells, promote the internalization and reduction of PD-L1, and protect T cells from immunosuppression.…”
Section: Omvsmentioning
confidence: 99%
“…Zou et al and Li et al both hybridized tumor cell membranes with OMVs to enhance the adaptive tumor immune response. , Moreover, according to Zhang et al, the thylakoid nanovesicle is another great choice to fuse with OMVs since it could enhance antitumor immunity via PDT effect . What’s more, Zhai et al demonstrated that OMVs could also be fused with photothermal sensitive liposomes to deliver siRNA for a combined photo/immunotherapy . Zhou et al developed a micromotor OMV (Figure d) to physically disrupt tumor tissue, recruit immune cells to process antigens from dead tumor cells, and elicit robust antitumor immunity .…”
Section: Immune Cell-based Drug Carriers For Cancer Immunotherapymentioning
confidence: 99%
“…256 What's more, Zhai et al demonstrated that OMVs could also be fused with photothermal sensitive liposomes to deliver siRNA for a combined photo/immunotherapy. 257 Zhou et al developed a micromotor OMV (Figure 9d) to physically disrupt tumor tissue, recruit immune cells to process antigens from dead tumor cells, and elicit robust antitumor immunity. 212 Li et al constructed PD-1-modified E. coli to collect OMV-PD-1 which could simultaneously provoke an immune response and block the PD-1/PD-L1-mediated T-cell exhaustion.…”
Section: Immune Cell-based Drug Carriers For Cancer Immunotherapymentioning
confidence: 99%
“…PTSLs can induce ICD by PTT and enhance the function of T cells by CD38 siRNA. Moreover, OMVs can enhance the immune response through their own adjuvant effect [123]. Wang's group and Chen's group both developed OMV-cancer cell member vesicle (OMV-CMV) nanoplatforms with PTT.…”
Section: Hybrid Nanovesicles In Cancer Immunotherapymentioning
confidence: 99%